2021
DOI: 10.21037/qims-20-610
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo vibro-acoustography characterization of osteoporosis in an experimental mice model

Abstract: Background: Osteoporosis is a highly prevalent multifactorial osteometabolic disease, classically diagnosed, in vivo, by dual energy X-ray absorptiometry (DXA). This study evaluated osteoporosis, ex vivo, using vibroacoustography (VA), an elastographic technique based on ultrasound radiation force.Methods: Three groups of mice femurs were used: (I) control group (CG), (II) osteoporosis group (OG) and (III) treated osteoporosis group (TOG), in which the animals received pamidronate, an antiresorptive drug. Eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Finally, in the pre-clinical sphere, vibro-acoustography (a technique based on ultrasound radiation) was able to differentiate between osteoporosis and control rodent groups; yet another potential future screening tool ( 67 ).…”
Section: Imagingmentioning
confidence: 99%
“…Finally, in the pre-clinical sphere, vibro-acoustography (a technique based on ultrasound radiation) was able to differentiate between osteoporosis and control rodent groups; yet another potential future screening tool ( 67 ).…”
Section: Imagingmentioning
confidence: 99%
“…A recent study has shown the potential of phalangeal Quantitative Ultrasonometry (QUS) for diagnosing osteoporosis on skeletal remains (Rinaldo et al, 2018). QUS is a reliable, portable, user‐friendly, and computer‐assisted clinical technique based on ultrasound waves propagation (Agnollitto et al, 2021; Baroncelli, 2008; Drozdzowska et al, 2005; Giavaresi et al, 2004; Guglielmi et al, 2015; Guglielmi & de Terlizzi, 2009; Hadji et al, 2015; Montagnani et al, 2000; Njeh et al, 1997; de Oliveira et al, 2011; Wüster et al, 2009, Wüster et al, 2005), which has never been applied before on forensic or archeological skeletal remains. In the paper of Rinaldo et al (2018), a protocol specifically adapted for skeletal remains and new reference curves were developed using a sample of 110 skeletons of known age and sex.…”
Section: Introductionmentioning
confidence: 99%